2022
DOI: 10.1161/svin.121.000292
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Effectiveness of Pipeline Shield Device for Intracranial Aneurysms in an Australian Cohort (SCOPE‐AUS)

Abstract: BACKGROUND The Pipeline Flex Embolization Device (PED) with Shield Technology (PED‐Shield) is a third‐generation flow diverting stents with surface modification designed to reduce platelet adhesion and thrombogenicity. We report the long‐term safety and effectiveness of the PED‐Shield in the treatment of unruptured intracranial aneurysms in an Australian cohort. METHODS SCOPE‐AUS (Safety and Clinical Effectiveness Of Pipeline Shield Embolization Device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The SCOPE-AUS study, which investigated the use of the PED device with Shield technology, reported complete aneurysm occlusion rates of 78.5% at 6 months and 92.5% (233/252) at 18 months or at last follow-up imaging, while the combined long-term neurologic morbidity and mortality occurred in 5% (12/238) of patients, with nine (3.8%) neurologic morbidities and three (1.3%) neurologic mortalities. 11 The authors also reported successful stent deployment in 97.3% (285/293) without the need for adjuvant balloon angioplasty. 11 In a separate study, Rice et al demonstrated high rates of complete occlusion (70.8% and 77.2% at 6 months and 1 year, respectively) and low rates of retreatment (0.05%) among subjects treated with the PED-Shield in the SHIELD study, while the morbidity and mortality rates were 3% and 1%, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The SCOPE-AUS study, which investigated the use of the PED device with Shield technology, reported complete aneurysm occlusion rates of 78.5% at 6 months and 92.5% (233/252) at 18 months or at last follow-up imaging, while the combined long-term neurologic morbidity and mortality occurred in 5% (12/238) of patients, with nine (3.8%) neurologic morbidities and three (1.3%) neurologic mortalities. 11 The authors also reported successful stent deployment in 97.3% (285/293) without the need for adjuvant balloon angioplasty. 11 In a separate study, Rice et al demonstrated high rates of complete occlusion (70.8% and 77.2% at 6 months and 1 year, respectively) and low rates of retreatment (0.05%) among subjects treated with the PED-Shield in the SHIELD study, while the morbidity and mortality rates were 3% and 1%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…11 The authors also reported successful stent deployment in 97.3% (285/293) without the need for adjuvant balloon angioplasty. 11 In a separate study, Rice et al demonstrated high rates of complete occlusion (70.8% and 77.2% at 6 months and 1 year, respectively) and low rates of retreatment (0.05%) among subjects treated with the PED-Shield in the SHIELD study, while the morbidity and mortality rates were 3% and 1%, respectively. 5 In addition, Trivelato et al reported 79.7% aneurysm occlusion at 6 months and 85.3% at 12 months, with a periprocedural complication rate of 7.3% among 151 patients with a total of 182 aneurysms treated with the PED-Shield.…”
Section: Discussionmentioning
confidence: 94%
“…This has also been reported in other cohorts reporting complete occlusion rates ranging from 70% to 90% in the mid and long term. 11,12,14,[19][20][21][22][23] A current landscape that is still a matter of debate concerns the safety profile of early discontinuation of DAPT or upfront aspirin monotherapy for patients treated with PED Shield. 18,24,31,32 Interestingly, in a small case series that included 14 patients with acute aneurysmal subarachnoid hemorrhage treated with Shield technology and aspirin monotherapy, only 1 case of instent thrombosis was reported, and it occurred the day after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to decreased platelet activation, proven in both in vitro and animal studies. 7,8 Since its Food and Drug Administration approval in 2021, many studies have evaluated the real-world safety and efficacy of PED with Shield technology, [9][10][11][12][13] However, there remains a paucity of literature comparing PED Shield to its predecessors, PED first-generation and PED Flex, which lack this surface modification. In our institution, PED with Shield technology was introduced in 2021 and, since then, has been the most common FD used in our practice.…”
mentioning
confidence: 99%
“…5,6 These refinements encompassed incessant technical modifications such as introducing new endoluminal devices, establishing intrasaccular flow divertors with the Woven EndoBridge (MicroVention Inc) being the prodigy of these devices, 7,8 and surface modifications feature of the existing devices such as Pipeline Embolization Device (PED) (Medtronic) Shield and the FRED-X devices. While large multicenter experiences are currently lacking from the United States, it is worth noting that thromboembolic rates reported from 3 international multicenter studies using the PED Shield (6.4%, 9 3.3%, 10 2.5% 11 ) were not different from earlier studies using prior PED versions (eg, Prospective Study on Embolization of Intracranial Aneurysms with the Pipeline Device 2.1% 12 and IntrePED 3.3% 13 ). Concurrently to the PED Shield, the FRED-X device features a similar nanopolymer surface modification aiming to reduce device thrombogenicity.…”
mentioning
confidence: 81%